Hubungan Culture Shock dengan Kesulitan Belajar Pada Siswa Kelas X SMK Negeri 8 Surakarta - Desyan Bagaskara, Muhammad; Hera Heru Sri Suryanti; Ahmad Jawandi (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
The purpose of this study was to identify and analyze the correlation between culture shock and learning difficulties at the tenth-grade students of SMKN 8 Surakarta in 2023/2024 academic year, to analyze the correlation between culture shock and students’ learning difficulties, to provide recommendations for school in overcoming culture shock and learning difficulties faced by students. The research data were collected using a questionnaire distribution that was divided into two, namely a questionnaire about culture shock and a questionnaire about learning difficulties. Data analysis in the study was carried out using correlational techniques to determine the strength of the relationship between the two variables. The results of the study showed that there was a significant relationship between culture shock and students’ learning difficulties. The higher the level of culture shock faced by students, the higher the learning difficulties experienced by them. Based on the results of the study, it could be explained that "there is a correlation between culture shock and learning difficulties of students in class X of SMKN 8 Surakarta in the 2023/2024 academic year." This was by knowing the r-count was 0.513. With a value of N = 30, the r-table value with a significance of 5% was 0.361 and 1% was 0.463. So, the conclusion was that the r- count is greater than the r-table with a significance level of 5% and 1% or 0.361 <0.513> 0.463. This finding indicated the importance of special attention to the impact of culture shock in the teaching and learning process.